KONTROVERSI KONTROVERSI PUBLIK DI MEDIA SOSIAL: KAJIAN ANALISIS WACANA KRITIS TERHADAP GUS MIFTAH - Awaliah, Qoni'Atul (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This research aims to analyze the public representation of Gus Miftah which gives rise to various responses and news narratives on social media and online media. This approach allows for three discourse dimensions related to the response, namely text dimensions, discourse practices and social practices. This research was conducted using descriptive-qualitative techniques that apply the Norman Fairclough model of critical discourse analysis approach. Data collection techniques are carried out by means of documentation, listening, transcription and language translation. The data source for this research was verified TikTok uploads and comments @Akuratco @Inilah.com from 30 November 2024 to 5 December 2024 which discussed responses regarding Gus Miftah's behavior which did not reflect a preacher. The data taken is in the form of phrases and sentences containing opinions to form discourse and public understanding in the response statement. The research results show that: 1) The text representation dimension, Gus Miftah's use of language displays typical preaching rhetoric which contains elements of morality, but gives rise to various interpretations in society, 2) The discourse practice dimension, an approach that helps understand how language functions in society, and 3) The dimensions of social practice, distribution and consumption of discourse through social media enable audiences to produce new meanings and create polarization of public perception in a socio-cultural context.